Analysis of Delays in the Construction Project of the Pumping House in the Sumenep District Using the Critical Path Method - John, Jenodius Aldino; Wulandari, Esti; Nugroho, Laksono Djoko (International Journal Labs, 2025)
Delays in construction projects pose significant challenges, particularly in remote areas like the Sumenep District. This research analyzed the pump house construction project delays using the Critical Path Method (CPM) to identify the primary factors causing delays, including material supply issues and labor shortages. A qualitative descriptive approach was employed, involving in-depth interviews with project stakeholders and analysis of project documents, including weekly reports and schedules. The findings indicated that the project experienced an average delay of two weeks, primarily due to delays in material supply from Surabaya and concurrent labor shortages caused by multiple simultaneous projects. To address these challenges, the study proposed solutions such as strengthening logistics coordination with local suppliers, increasing the workforce on critical tasks, and utilizing additional heavy equipment. The implications of this research highlight the importance of effective time and resource management in construction projects, particularly in remote locations. Applying the CPM method, this study identifies the root causes of delays and provides practical strategies to enhance project efficiency and reduce costs. This research contributes to the existing literature on construction management in Indonesia, emphasizing the need for adaptive approaches tailored to local conditions.